Legal Reconstruction and Polygamy Problems in Sharia Maqashid and Positive Law Perspectives - Sugianto Sugianto; Abdurohim Abdurohim; Oriza Aditya (Journal of Social Science)
Marriage in principle is for peace in society in which it forms a joint commitment in forming a common goal, some are monogamous or have one wife and some are polygamous, namely more than one wife. Polygamy is indeed allowed in Islam and Positive Law, but with conditions that must be met. The state also allows the practice of polygamy with conditions that must be met, not much different from religious rules. Therefore, if a person wishes to practice polygamy, he must understand the rules in religion and the state so that it is also recorded by the state. This study aims to determine legal reconstruction and polygamy problems in Sharia Maqhosid presfectives in West Java. The research method used is qualitative research. Polygamy taught in Islamic law is for good, not for damage by protecting religion, lineage, reason, property and self-esteem as a solution to social problems in society from these problems. It is positive because it sees phenomena and existing legal facts so that with maqoshid sharia it can make a meaningful contribution.